MEMBANGUN KESADARAN ANTI-BULLYING MELALUI LAYANAN BIMBINGAN KELOMPOK (Studi Pelaksanaan di SMA Islam Al Ulum Terpadu Medan) - Wan Hanis Masfufah Al; Uli Makmun Hasibuan; Tasya Putri Cahaya; Dwi Atika Zahra (Kampus Akademik Publiser, 2026)
Bullying in the school environment is a serious problem that has a broad impact on students' mental health and academic achievement. This article describes the implementation of Group Guidance (BKp) services with an anti-bullying theme which was carried out in a special room at the Al Ulum Integrated Islamic High School in Medan involving three female students from the Muhammadiyah University of North Sumatra, Wan Hanis, Tasya, and Dwi Atikah and five students as active participants. Activities are designed using four stages of BKp services: formation, transition, core activities, and termination. The formation stage begins with greetings, introductions between counselors and participants, and reading prayers. After that, Wan Hanis asked questions about the meaning of bullying to explore the participants' initial understanding, followed by delivering material using image poster media displayed on an Android tablet, covering the meaning of bullying, forms of bullying, the consequences of bullying for perpetrators, victims and schools, the causes of bullying, and how to prevent it. The participants responded actively and critically, revealing their experiences and views on the phenomenon of bullying at school. Observation results show increased understanding and the emergence of a collective commitment to creating a safe school environment. This article confirms that the structured BKp intervention is effective as a medium for primary prevention of bullying in secondary schools.